Effect of modeling femoral version and head-neck offset correction on computed contact mechanics in dysplastic hips treated with periacetabular osteotomy. (August 2022) - Aitken, Holly D.; Westermann, Robert W.; Bartschat, Nicholas I.; Clohisy, John C.; Willey, Michael C.; Goetz, Jessica E.
Abstract: While correction of dysplastic acetabular deformity has been a focus of both clinical treatment and research, concurrent femoral deformities have only more recently received serious attention. The purpose of this study was to determine how including abnormalities in femoral head-neck offset and femoral version alter computationally derived contact stresses in patients with combined dysplasia and femoroacetabular impingement (FAI). Hip models with patient-specific bony anatomy were created from preoperative and postoperative CT scans of 20 hips treated with periacetabular osteotomy and femoral osteochondroplasty. To simulate performing only a PAO, a third model was created combining each patient's postoperative pelvis and preoperative femur geometry. These three models were initialized with the femur in two starting orientations: (1) standardized template orientation, and (2) using patient-specific anatomic landmarks. Hip contact stresses were computed in all 6 model sets during an average dysplastic gait cycle, an average FAI gait cycle, and an average stand-to-sit activity using discrete element analysis. No significant differences in peak contact stress ( p  = 0.190 to 1), mean contact stress ( p  = 0.273 to 1), or mean contact area ( p  = 0.050 to 1) were identified during any loading activity based on femoral alignment technique or inclusion of femoral osteochondroplasty. These findings suggest that presence of abnormal femoral version and/or head-neck offset deformities are not themselves predominant factors in intra-articular contact mechanics during gait and stand-to-sit activities. Inclusion of modified movement patterns caused by these femoral deformities may be necessary for models to adequately capture the mechanical effects of these clinically recognized risk factors for negative outcomes.